A progressive breakdown of the body in space. Issue 3 (4th May 2018) - Kourtidou, Evie; Kasselimis, Dimitrios; Makrydakis, George; Chatziantoniou, Lina; Kyrozis, Andreas; Evdokimidis, Ioannis; Potagas, Constantin
ABSTRACT: A 74 year-old woman (MD), free of previous neurological history, presented with difficulty in handling cutlery, clothes, writing with what was initially described as an atypical apraxia in acts related to space. Initial neurological evaluation revealed mixed, asymmetric pyramidal, and extrapyramidal semiology. Νeuropsychological testing revealed dressing and constructional deficits, ideomotor apraxia and signs of executive dysfunction in absence of memory, language, and visual perception pathology. The final diagnosis was that of a corticobasal degeneration, where the rare occurrence of a progressively emerging syndrome of self-management loss within peripersonal space is observed.